Criteria for selecting volleyball team captain on the signs of their leader behavior - Nikolaev, A. N.; Shlat, N. Yu.; Anufryienko, L. V.; Shalak, O. M. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to experimentally substantiate the dependence of the cohesion of sports teams, the success of their performances, as well as the development of the personality of young volleyball players, on the degree of severity of the captains of these teams' propensity for various leadership options.